(untitled) (LEARNing Landscapes, 2008)
This paper describes how works created in a visual arts workshop enable the author to work obliquely with stories about teaching Aboriginal children generated in a collective biography. The deconstructive work is framed by Prime Minister Rudd’s 2008 "sorry" speech to Aboriginal Australians and Mazzei’s work on silence with white teachers. The visual arts methodology allows a shift from narrative logic and literal detail to metonymy and symbolism while the materiality of artefacts and art equipment invite particular representations and interpretations to emerge.